A STUDY OF FINANCIAL PLANNING OF INDONESIAN FAMILY LIVING IN KUALA LUMPUR, MALAYSIA - Arsyianti, Laily Dwi (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2011)
Many related studies have been conducted in various developed countries and East Asia countries, but rarely in developing countries, including Indonesia. This study focuses on financial planning of Indonesian families living in Kuala Lumpur, Malaysia. Furthermore, gender and spirituality aspects will be studied regarding the financial decision making in the families and savings and investment pattern will be investigated. The desired objectives that want to be achieved by this research are as follow: to study the pattern of financial decision making made by Indonesian families living in Kuala Lumpur; to investigate the savings and investment planning activities of Indonesian families living in Kuala Lumpur; and to examine the impact of religiosity on their financial decisions. Primary data was obtained through interview method. The interviews were conducted to 10 Indonesian Muslim families. Each couple has their own unique financial planning behaviour. However, among this unique behaviour, there are some redline principles that can show particular pattern, but still, its possibility to generalize the pattern is not that accurate. Consequently, further study regarding the uniqueness behaviour of families living in or originally from developingcountries has to be more investigated to find out what are the rationale behind the scene.